Defending What You Believe: What you believe is worth defending - Afolabi, Ebenezer (CreateSpace Independent Publishing Platform, 2014)
"Christianity will always be attacked," says Ebenezer Afolabi. It is therefore the duty of every believer to take up the task of defending what they believe. This book is divided into two interesting sections where you can learn how to be empowered to defend your faith. In the first section, the author discloses the conflicting and erroneous presuppositions of the major Christian groups in the world, their strengths and weaknesses, and how to deal with them. In the second section you will also learn more about Jesus Christ, His historicity, His deity and humanity, and what other religions and historical documents say about Him. Furthermore, the author reveals the methods used by skeptics to attack the Christian faith, and also suggest eight practical tools Christians can use to expose and refute all erroneous claims. This is a book you cannot afford to miss. Please consider posting a review after reading this book. This will be greatly appreciated.
paid